Why the left loses : the decline of the centre-left in comparative perspective / edited by Rob Manwaring and Paul Kennedy. - Manwaring, Rob; Kennedy, Paul (Policy Press, 2018)
Bringing together a range of leading academics and experts on social democratic politics and policy, Why the Left Loses offers an international, comparative view of the changing political landscape, examining the degree to which the centre-left project is exhausted and is able to renew its message in a neo-liberal age.